The legacy of muscular Judaism: Jewish-Israeli identity through sport - Hancock, SP (2018)
This thesis examines how Israel’s identity as a Jewish state is expressed through sport, using both archival and historical sources and ethnographic fieldwork. My primary contribution to the literature builds upon the history of muscular Judaism in order to develop a longitudinal perspective demonstrating how the body continues to provide a source of social and political capital, both reflecting and confronting identity. I show how sport is a platform for identity negotiation, a position which necessarily confronts certain other issues, including ethnoreligious divisions, Jewish sectarianism, nationalism and Israeli control of the Palestinian territories. Consequently, a second focus is the degree to which sport may be used for normalising relationships within Israel, primarily, secular Jewish-Israeli and Palestinian- Israeli relationships. I explore the nexus of sport and identity within Israel through three ethnographic chapters, each exploring different themes through expanding but interconnecting perspectives within local, national and international spheres respectively. In the first ethnographic chapter (4), I show how community-based sport fits within the greater normalisation debate, viewing its successes and failures in response to the prevailing Jewish state. As professional football has had an integral role in modern Israeli history, Chapter 5 takes a fresh perspective on football culture, primarily seeing fans as a form of scaffolding upholding state institutions. The final ethnographic chapter (6) looks beyond Israel’s borders, adopting the perspective of the state to see how athletes legitimise and broker Jewish identity on an international scale. Ultimately, I find that, akin to Nordau’s concept of muscular Judaism, sport continues to be productive for negotiating identity within Israel. Sport, however, reflects underlying socio-political patterns, and as such, the different areas of sport explored in the respective chapters have complementary strengths and spheres of influence for confronting and brokering Jewish-Israeli identity with the Diaspora, the Arab Middle East and recursively with itself.